The Use of Social Media Platforms by Road Safety Personnel for Advocacy Programmes on Traffic Regulations in Nigeria - MUKHTAR, HABIBU; MAIDABINO, A. A. (MiddleBelt Journal of Library and Information Science, 2020)
This study investigates the use of SM platforms by road safety personnel in public advocacy programmes on traffic regulations in Jigawa State Nigeria. The study used quantitative research method and adopted a correlational research design. Structured questionnaire was used for data collection from 198 respondents comprising road safety personnel serving in Jigawa State. Frequency distribution table, correlation coefficient and multiple regression analyses were carried out on the data collected. Findings revealed that, respondents are aware of SM platforms and use them for public advocacy on traffic regulations. Facebook, WhatsApp, Twitter and Youtube are the types of SM platforms used by the respondents. On the hypothesis tested the study found that, ditto there is significant relationship between the awareness and use of SM platforms. The study concludes that, road safety personnel are aware of, and used four types of SM platforms for public advocacy. The study recommends that, Federal Road Safety Corps (FRSC) should adopt and support the use of SM for public enlightenment through reward and inceptives to serve as an encouragement and motivation to their personnel in order to facilitate the use of SM platforms so as to educate road users and reduce road traffic crash to the barest minimum.